2017
DOI: 10.1289/ehp1318
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic Effects and Gene Expression Profiling of Firemaster® 550 Components in Human Primary Preadipocytes

Abstract: Background:Exposure to flame retardants has been associated with negative health outcomes including metabolic effects. As polybrominated diphenyl ether flame retardants were pulled from commerce, human exposure to new flame retardants such as Firemaster® 550 (FM550) has increased. Although previous studies in murine systems have shown that FM550 and its main components increase adipogenesis, the effects of FM550 in human models have not been elucidated.Objectives:The objectives of this study were to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Like in 3T3-L1 cells and in mice in vivo, TPhP fails to induce brite adipocyte differentiation in primary human preadipocytes. In accordance with a previous study (Tung et al 2017b), TPhP induced lipid accumulation and expression of white adipocyte genes (i.e. Plin1 and Cidec).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Like in 3T3-L1 cells and in mice in vivo, TPhP fails to induce brite adipocyte differentiation in primary human preadipocytes. In accordance with a previous study (Tung et al 2017b), TPhP induced lipid accumulation and expression of white adipocyte genes (i.e. Plin1 and Cidec).…”
Section: Discussionsupporting
confidence: 93%
“…OPEs and their metabolites are ligands for multiple human nuclear receptors (Kojima et al 2013(Kojima et al , 2016. There is strong evidence that TPhP is a peroxisome proliferator-activated receptor γ (PPARγ) ligand and is adipogenic (Belcher et al 2014;Fang et al 2015;Pillai et al 2014;Tung et al 2017aTung et al , 2017b. TPhP induced lipid accumulation and perilipin (lipid droplet marker) protein expression in mouse BMS2 cells and increased adipocyte protein 2 (aP2) mRNA expression in mouse 3T3-L1 adipocytes (Pillai et al 2014;Tung et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the strongest argument raised against the transmission of epigenetic marks such as DNA methylation is that genome-wide epigenetic reprogramming in mammalian germline cells should erase epimutations from the preceding T A B L E 1 List of known obesogens and potential obesogens with selected end-points and references. The reader should also consult references in previous review articles 46,121 Major use category 131,132 Triphenyl Phosphate + + Lipid accumulation; increased body-weight and fat mass in mice 134,135 FM-550 + + Lipid accumulation; weight gain 134,135,137,138 Pesticide Chlorpyrifos + Weight gain and hyperinsulinemia in rats 141,142 Quinoxyfen + Induce adipogenesis and adipogenic gene expression in 3T3-L1 cells 90 Forchlorfenuron + Induce adipogenesis and adipogenic gene expression in 3T3-L1 cells 90 Flusilazole + Induce adipogenesis and adipogenic gene expression in 3T3-L1 cells generation. 111,112 Some investigators report stable transgenerational changes in DNA methylation 110,114,115 ; others found that the same chemicals induced epimutations and alterations in gene expression in the F1 generation, but that these were not conserved in F2 prospermatogonia.…”
Section: Obesogens Can Be Heritablementioning
confidence: 99%
“…We also identified mechanistic evidence pointing towards an effect of TPhP and TBBPA on metabolic disorders but only very few studies addressed these adverse effects in animal models or in humans. For example, several in vitro studies reported adipogenesis and/or lipid accumulation and two studies showed increase in body weight associated with TPhP exposure in humans and rodents, and with TBBPA exposure in fish [6,35,52,55,56,65,66,70]. In addition, activation of PPARγ (the MIE of AOP 72 that leads to obesity) by TPhP and TBBPA has been reported in many in vitro studies, two ToxCast assays and in zebrafish, with effective doses below 1 µM for TBBPA only (for example: [17,54,55]).…”
Section: Possible Aos Of Cat I Frs Predicted From Aop Searchmentioning
confidence: 99%